Association between serum vitamin D and depressive symptoms among female workers in the manufacturing industry. Issue 1 (December 2015) - Kwon, Soon; Son, Jun; Kim, Young; Chae, Chang; Kim, Ja; Kim, Chan; Park, Hyoung; Lee, Jun; Jung, Jun
Abstract Background Vitamin D has been known to maintain the body's balance of calcium and phosphorus as well as skeletal health. There has been increasing emphasis on the importance of vitamin D as recent studies have been reporting the specific functions of vitamin D in the cerebral nervous system and the association between the level of serum vitamin D and depressive symptoms. However, there is currently a paucity of research investigating the association between serum vitamin D and depressive symptoms in Korean subjects. Consequently, this study has aimed to determine the level of serum vitamin D and explore the association between serum vitamin D and depressive symptoms in Korean female workers. Method A medical examination, questionnaire, anthropometric measurements, and a blood test were conducted between February 3 and March 7, 2014 in 1054 subjects among female workers in the manufacturing industry who underwent physical examinations in a university hospital. From this data, we identified the level of serum vitamin D and investigated the association between serum vitamin D deficiency and depressive symptoms. Results The average serum vitamin D level of the 1054 subjects was 9.07 ± 3.25 ng/mL, and the number of subjects in the serum vitamin D deficiency group with less than 10 ng/mL was 721 (68.4 %). The odds ratio of the depressive symptom group with a CES-D score of 16 or above being in the deficiency group with a serum vitamin D level less than 10 ng/mL was found to be 1.55 (95 % CI = 1.15–2.07). Conclusion 68.4 % of female workers in the manufacturing industry were in the deficiency group with serum vitamin D levels less than 10 ng/mL. Additionally, we identified an association between serum vitamin D deficiency and depressive symptoms. In the future, if serum vitamin D deficiency is checked regularly in workers, we expect to achieve better outcomes in managing their depressive symptoms.